Medieval canon Law - Brundage, James A., author.
1 online resource.
Keywords: "It is impossible to understand how the medieval church functioned, and in turn influenced and controlled the lay world within its care, without understanding 'canon law'. This book examines its development from its beginnings to the end of the Middle Ages, updating its findings in light of recent scholarly trends and a deeper look at the sources of law. Covering all aspects of medieval canon law and its influence on medieval politics, society and culture, this book provides students of medieval history with an accessible overview of this foundational aspect of medieval history"--